The Evolution of Hominin Diets Integrating Approaches to the Study of Palaeolithic Subsistence - Hublin, Jean-Jacques; Richards, Michael P. (Vertebrate Paleobiology and Paleoanthropology, 2009)
This volume brings together new and important research from the top experts in hominid diets across multiple fields. The objective of the volume is to explore if there is a consensus between the different methods, allowing us to better understand the nature of hominin dietary strategies through time. Contributions focus on modern studies, faunal studies, physical anthropology, archaeological studies, and isotopic studies, all aimed at answering the major questions of the evolution of hominid diets, such as: meat-eating emergence, hunting vs. scavenging, hunting technologies, and resource intensification in later humans.